KEPATUHAN MINUM OBAT ANTI RETRO VIRAL (ARV) PADA PASIEN HIV/AIDS - Yanto Suryanto; Uun Nurjanah (Jurnal Ilmu Keperawatan Indonesia, 2021)
Adherence to Anti Retro Viral (ARV) therapy is the key to successful treatment of HIV infection, because continuous ARV can suppress HIV to its undetectability, reduce the risk of drug resistance, improve quality and survival, improve overall health and reduce the risk of HIV transmission. Conversely, non-adherence to treatment is a major cause of treatment failure. The aim of this study is to identify factors that related to adherence of drinking Anti Retro Viral drugs (ARV) in HIV patients at Karawang Local General Hospital in 2019. The design used  cross – sectional,  using total sampling as many as 115 respondents. The statistical test used  chi – square test. The results obtained there is a relationship between knowledge and adherence of drinking Anti Retro Viral (ARV) drugs (ρ value 0,023 < α 0,05). There is a relationship between self – efficacy and adherence of drinking Anti Retro Viral (ARV) drugs (ρ value 0,024 < α 0,05 ) and there is a relationship between family support and adherence of drinking Anti Retro Viral (ARV) drugs (ρ value 0,007 < α 0,05). The recommendation is the need for family involvement as Drug Swallowed Supervisor (PMO) and peer group involvement and support from health workers in increasing medication adherence.